The Strategies Of The Teacher In Motivating The Students In Learning English At Eleventh Class Study Of MA AL Hasyimiyah Academic Year 2020/2021 - Semaria Eva Elita Girsang; Siti Chadijah (Program Studi Pendidikan Bahasa Inggris FKIP, 2022)
This research aim to to find out English teacher’s strategies to increase the students motivation in learning English and to find out the students’ responses to the English teacher’s strategies to increase the motivation in learning English. The researcher made preliminary observation on students at class XI MA Al Hasyimiyah. The location of this school is on Danau Singkarak Street, Tebing Tinggi. The researcher used the descriptive qualitative method. The technique of collecting data applies in the research are Observation, Interview to the teacher and completes by distributing a que stionnaire. Based on the research result, English teachers use interesting learning or varied methods to overcome the different characters of children in learning English. in this case, this finding is supported by Sadirman A.M (2009:91) strategies in motivating the students, there are eight strategies but the teacher just use four strategies, such as Explain learning Objectives to student, helping the learning difficulties of student individually or in groups, arousing student’s interesting, and give praise for each student’s success, and The response of class XI MA AL Hasyimiyah students to the teacher are quite satisfying, and open minded